Using Verb Search Combined with Picture Series for Teaching of Narrative Text to the Tenth Grade Students (RETAIN, 2016)
Using Verb Search Combined with Picture Series for Teaching of Narrative Text to the Tenth Grade Students Fajar Kumala Pendidikan Bahasa Inggris FBS Universitas Negeri Surabaya (fajarkumala05@gmail.com) pembimbing Him’mawan Adi N., S.Pd.,M.Pd. Pendidikan Bahasa Inggris FBS Universitas Negeri Surabaya (himmawan_95@yahoo.co.id) Abstract Verb search is a kind of game that can be use a media to teaching grammar especially past tense (Tsuwayroh in Stiawan 2015). The original form of verb search consists of a column and a free shape (big square, big question mark, or other shapes) that shaped in a paper. In this research, the teacher used the verb search combined with picture series. Picture series here means a series or sequence of events that tells a narrative. The aim of this media is used to obtain a deep understanding of learning supporting competences of the narrative text as the basis of the students to make a narrative text. Therefore, this research aims to know how this media is used to teach writing narrative text and to know the students’ opinions toward the use of this media in the teaching of writing narrative text. Research Design of this study was desciptive qualitative. The instrument which is used in this study is questionnaires and observation sheet .The data analysis technique done through three steps, they are: data reduction, data display, and conclusion drawing/verification(Miles and Huberman, 1994). The result of this study showed that the students enjoyed learning narrative text by using verb search combine with picture series. This media was an effective way to make the students interested in the material. The students were enthusiastic to follow the teaching learning process although there was student felt sleepy in the classroom. In this study, the teacher did three activities in each three meetings those were exploration, elaboration, and confirmation. Key words: Verb Search, Picture Series, Writing, Narrative Text Abstrak Verb search adalah sejenis permainanyang dapat digunakan sebagai media pembelajaran grammar khususnya past tense ((Tsuwayroh in Stiawan 2015). Verb search berbentuk lembaran. Bentuk asli dari verb search terdiri dari sebuah kolom dan sebuah bentuk bebas (dalam bentuk persegi yang besar, tanda tanya yang besar, atau bentuk lainnya) yang dikemas dalam lembaran kertas. Dalam penelitian ini, guru menggunakan verb search yang dikombinasi dengan picture series. Gambar berseri adalah kumpulan dari kejadian-kejadian yang menceritakan tentang cerita naratif. Tujuan dari media ini adalah untuk memperoleh pemahaman yang mendalam tentang pembelajaran supporting competences dari teks naratif sebagai fondasi siswa dalam membuat teks naratif. Oleh karena itu, penelitian ini bertujuan untuk mengetahui bagaimana media ini diterapkan dalam pembelajaran menulis teks naratif dan untuk mengetahui opini dari siswa terhadap penggunaan media dalam pembelajaran menulis teks naratif. Desain penelitian ini menggunakan deskriptif kualitatif. Instrument penelitian yang digunakan dalam penelitian ini adalah angket dan lembar obserfasi. Teknik menganalisis data dilakukan dalam tiga tahap, yaitu: pengurangan data, mempertunjukkan data, dan kesimpulan/verifikasi (Miles and Huberman, 1994). Hasil dari penelitian ini menunjukkan bahwa siswa menikmati belajar teks naratif dengan mengguanakan verb search yang dikombinasikan dengan gambar berseri. Media ini adalah sebuah cara yang efektif untuk membuat siswa merasa tertarik dengan materi pelajaran. Siswa merasa antusias untuk mengikuti proses belajar mengajar meskipun ada juga siswa yang mengantuk dikelas. Dalam penelitian ini, guru melakukan tiga tahapan dalam setiap pertemuan, tahapan tersebut adalah eksplorasi, elaborasi, dan konfirmasi. Kata Kunci: Verb Search, Picture Series, Pengajaran menulis, Teks Naratif